BPOM's Role in Muslim Consumer Protection Against Non-Halal Medicines - Romli, Rido’i Aka; Hardyansah, Rommy; Saputra, Rio (Journal of Social Science Studies, 2023)
Monitoring the circulation of non-halal medicines in Indonesia is a crucial issue that requires serious attention, especially in the context of Muslim consumer protection. The Food and Drug Supervisory Agency (BPOM) has a strategic role in ensuring that drugs in circulation meet safety, quality, and halal standards. This study aims to analyse the effectiveness of supervision carried out by BPOM in tackling the circulation of non-halal drugs, with reference to the provisions of BPOM Regulation Number 20 of 2021 and other supporting regulations. The method used is a normative juridical approach with literature study as the main source of data. The results of the analysis show that the effectiveness of BPOM supervision still faces a number of obstacles, including limited supervisory staff in the field, low consumer awareness of the importance of halal labelling, and weak enforcement of administrative sanctions. In addition, challenges also arise in the form of the lack of synergy between institutions involved in the halal product guarantee system. This study recommends strengthening regulatory aspects, more massive public education, and providing incentives to producers to encourage compliance with halal certification. A more structured collaboration between BPOM, BPJPH, MUI, and the industrial sector is also key in realising an effective monitoring system. With a comprehensive approach, BPOM is expected to optimise its function in protecting consumers and ensuring the halalness of pharmaceutical products in Indonesia.